Effectiveness of Grow Me Coaching Model Module on Improving Self Efficacy in Laboratory Learning of Nursing Students - Nunik Purwanti; Ayu Isnawati; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2025)
Laboratory practice is a skill, knowledge, and attitude training exercise designed to help students comprehend professional nursing competencies. Students' capacity to learn the content can be impacted by low levels of self-efficacy. Numerous research have demonstrated that student learning strategies can raise self-efficacy. To increase student self-efficacy, a variety of teaching strategies can be employed; in this study, the model Grow Me coaching module. Research methods: The type of research used is quantitative quasi-experimental research with a nonequivalent control group design approach. The population of this study were all D3 Nursing students in the 3rd semester of the 2024 academic year, totaling 58 students. The research used a simple random sampling method, namely using the Slovin equation with a sample size of 50 students. This study was divided into 2 groups, namely the control group and the mediation group. The variables in this study are the Grow Me Coaching Model Learning Module as the independent variable and student self-efficacy during practicum at the health center as the dependent variable. The research instrument was the Grow Me Coaching Model Module given to students and the GSE questionnaire to measure the level of student self-efficacy. Data examination was carried out using the Wilcoxon Sign Rank test with significance <0.05. Result: Examination of the frequency distribution of respondents based on the level of self-efficacy progress using the Wilcoxon Marked Rank Test in the intervention group obtained a significance value (p) = 0.000 smaller than α = 0.05, while in the control group obtained a significance value (p) = 0.317 greater than α = 0.05, meaning that there is a sufficient influence between the Grow Me Coaching Model Learning Module and increased self-efficacy in learning the infusion installation laboratory in nursing students. Conclusions: The results of this study are the implementation of the coaching module based on the GROW ME model, proven effective in improving the self-efficacy of nursing students in laboratory learning.